Mitochondrial basis of the anti‐arrhythmic action of lidocaine and modulation by the n‐6 to n‐3 PUFA ratio of cardiac phospholipids. (24th February 2012) - Demaison, Luc; Moreau, Daniel; Clauw, Fabienne; Vergely, Catherine; Rochette, Luc
Abstract The aim of this study was to evaluate the involvement of mitochondria in the mechanism of the anti‐arrhythmic lidocaine. Rats were fed with a diet containing either n‐6 polyunsaturated fatty acids (PUFAs, SSO group) or an equimolecular mixture of n‐3 and n‐6 PUFAs (FO group) for 8 weeks. The hearts were perfused according to the working mode using a medium with or without lidocaine 5 μm. They were then subjected to local ischemia (20 min) and reperfusion (30 min). Dietary n‐3 PUFAs triggered the expected decrease in the n‐6/n‐3 PUFA ratio of cardiac phospholipids. Reperfusing the ischemic area favored the incidence of severe arrhythmias. Lidocaine treatment abolished almost completely reperfusion arrhythmias in the FO group, but did not display anti‐arrhythmic properties in the SSO group. As it was indicated by measurements of the mitochondrial function, lidocaine seemed to favor mitochondrial calcium retention in the FO group, which might prevent cytosolic calcium spikes and reperfusion arrhythmias. In the SSO group, the resistance to lidocaine was associated with an aggravation of cellular damages. The mitochondrial calcium retention capacities were saturated, and lidocaine was unable to increase them, making the drug inefficient in preventing reperfusion arrhythmias.